2005
DOI: 10.1007/s00412-005-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

How did the platypus get its sex chromosome chain? A comparison of meiotic multiples and sex chromosomes in plants and animals

Abstract: The duck-billed platypus is an extraordinary mammal. Its chromosome complement is no less extraordinary, for it includes a system in which ten sex chromosomes form an extensive meiotic chain in males. Such meiotic multiples are unprecedented in vertebrates but occur sporadically in plant and invertebrate species. In this paper, we review the evolution and formation of meiotic multiples in plants and invertebrates to try to gain insights into the origin of the platypus meiotic multiple. We describe the meiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 92 publications
(112 reference statements)
2
59
0
Order By: Relevance
“…Other gene blocks on the platypus sex chromosomes have homology to other chicken chromosomes, consistent with the derivation of platypus chain by sequential translocations with autosomes 53. Sequence comparisons between X‐Y shared genes revealed that the large X 5 and tiny Y 5 that terminate the chain are the most diverged, and therefore the oldest members of the chain 54, suggesting that they represent the original mammalian sex chromosomes.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionsupporting
confidence: 53%
“…Other gene blocks on the platypus sex chromosomes have homology to other chicken chromosomes, consistent with the derivation of platypus chain by sequential translocations with autosomes 53. Sequence comparisons between X‐Y shared genes revealed that the large X 5 and tiny Y 5 that terminate the chain are the most diverged, and therefore the oldest members of the chain 54, suggesting that they represent the original mammalian sex chromosomes.…”
Section: Platypus Sex Chromosomes Rewrote Mammal Chromosome Evolutionsupporting
confidence: 53%
“…Since F 1 females have 24 chromosomes, we find that the normal autosome is indeed inherited with the X chromosome and acts as a neo-X. Alternate segregation is seen in other species with multiple sex chromosomes that form a chain (Gruetzner et al 2006). For example, in the dioecious species in Rumex section Acetosa having two Y chromosomes and a single X these three chromosomes form a trivalent, Y1-X-Y2, and gametes containing either the X or Y1 and Y2.…”
Section: Resultsmentioning
confidence: 67%
“…In animals these configurations may include sex chromosomes, resulting in the formation of multiple X and Y chromosomes. For example, the monotreme platypus possesses five X and five Y chromosomes that form a chain of alternating X and Y chromosomes in male meiosis (Bick and Sharman 1975;Gruetzner et al 2006). Such chains are formed due to several interchromosomal translocation events, including sex chromosome-autosome translocations (Gruetzner et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meiotic multiples of more than four chromosomes are rare, and most of these cases are confined to plants and invertebrates, having never been described in fish (for review, see Grü tzner et al, 2006). Until this study, the biggest chromosomal chains detected in vertebrates were observed in platypus males (Ornithorhynchus anatinus) that have five X and five Y chromosomes.…”
Section: Discussionmentioning
confidence: 94%